Improving Adherence to Prolactin Monitoring Guidelines in Acute Psychiatric Wards - Hannah Campling; Kimia Ghaderi; Jayana Patel (BJPsych Open)
Aims: The purpose of this project was to improve clinician’s understanding and adherence to prolactin monitoring guidelines among doctors, reducing unnecessary testing and ensuring appropriate management of hyperprolactinaemia in patients on antipsychotic medications.